Trade policy and integration among firms producing complementary products - Medrano, Leonardo (Estudios Económicos de El Colegio de México, 2001)
This paper studies the effects on insurance premiums and consumer welfare when commissions to insurance agencies exist and are used strategically to sell insurance policies. The opportunistic behavior of agency insurers that sell the policy paying the highest commission is considered. Different market structures are considered, namely, a duopoly of insurers that compete in commissions (insurer competition), collusion among insurers with agency insurers remaining independent (horizontal collusion or insurer monopoly) and collusion between insurers and agency insurers (vertical integration or exclusive agents). We fins that insurer competition and vertical integration trigger higher premium than horizontal collusion with independent agencies. Furthermore, we argue that the optimal commission from the consumer viewpoint may be greater than the commission offered under any of the above three market structures.